GEOMORPHOLOGY OF BELEN PERCHED SYNCLINES (AMANOS MOUNTAINS, HATAY) - Emre ÖZŞAHİN (Fırat University, 2019)
During geomorphologic development, different landforms are occur or eliminated. This condition isn’t mention about at several times due to some exception the events and, geomorphologic cycle is occur some lanfdform inversion. One of the most striking ones this kind of inversion is perched synclinals. Perched synclinals are formed by potamic erosion and discharge of the previously higher anticlinals down to levels lower than the synclinals in the area. This study tries to explain formation and geomorphologic characteristics of two the perched synclinal where are found on the Amanos Mountains (Middle Amanos Mountains) in Hatay province at the southmost portion of Turkey. In addition to related literature, the study utilized the 1/25.000 scale topography map (O36c4, O36c3, P36a2, P36b1) prepared by General Command of Mapping (GCM) as basic material. The layers of this map sheet titled “Elevation_1” and “Hydrography_1” were digitally used in DVD in WGS-84 datum and Arc Info Coverage format and converted into vector format. Geological characteristics were compiled from geological maps of various scales prepared by different researchers. In addition, the datas obtained with the help of the maps, was used to field works. Results show that Belen perched synclines developed in bed rock in the Middle Miocene reef limestone lithology. The existence of the perched synclines in the area shows that the region is currently in the period of maturity; that the Amanos Mountains identified today as horst previously had a folded structure and that they had risen with a high tempo to obtain the current character. Further studies on identification of other geographical formations of the same type will contribute to better understanding of the geological background of the Amanos Mountains and interpretation of the paleo-geography of the region more correctly.